Anestesia general para cesárea en paciente con paraparesia espástica asociada al virus linfotrópico de las células T humanas tipo 1 - Calderón, Marjorie Lisseth (2021)
Introduction: Spastic paraparesis is an infection caused by the human T-cell lymphotropic virus (HTLV-1). It is characterized by slow onset myelopathy that mainly compromises the lower limbs.  It affects women more than men and the main routes of transmission are: blood, sexual and vertical (mainly during breastfeeding). Case presentation: Pregnant, 28 years of age, and 38 weeks of gestation, with a diagnosis of spastic paraparesis associated with HTLV-1; scheduled for the cesarean section; in whom a balanced general anesthetic technique was employed.  Conclusions: Balanced general anesthesia was a reasonable option for the anesthetic management of cesarean section in this patient, providing adequate muscle relaxation during surgery, with minimal hemodynamic changes, as well as a rapid recovery from neuromuscular blockade.